Effect of cold storage on the performance of Trichogramma bourarachae (Pintureau and Babault) (Hymenoptera: Trichogrammatidae - Abbes, Khaled; Zouba, Anis; Harbi, Ahlem; Chermiti, Brahim (Cairo University, 2020)
In Tunisia, the use of the egg parasitoid trichogrammatid wasps to cope with several economic pests is gaining increasing attention. Trichogramma bourarachae (Pintureau & Babault) is among the Trichogramma wasps naturally present in Tunisia and regarded as a potential natural enemy to be used in biological control programs of many lepidopteran pests that cause economic losses. The propensity of T. bourarachae to cold storage with and without diapause induction was studied. The effect of this technique on its emergence rate and parasitic activity was investigated. The study showed that wasps of T. bourarachae treated at the induction temperature of 15 °C for 5 days can be stored at 4 ± 1 °C for more than 30 days without significant loss of their performances. By using this prestorage temperature, T. bourarachae could keep its emergence capacity (77.5%) up to 60 days of cold storage at 4 ± 1 °C. However, its parasitic activity decreased significantly (37.16%) after 45 days of cold storage. These results are promising for its mass production, transport, and release in the framework of national campaigns to control several agricultural pests of economic importance.